COINTEGRATION AND CONTAGION EFFECT CONVENTIONAL AND SHARIA STOCK INDICES DURING COVID-19 - Novianti, Diah; Amalia, Feby Ayu (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2023)
The COVID-19 pandemic has also affected stock price movement all over the world, along with the changes in the economic sector. Many studies have tried to reveal the integration of stock indices worldwide, but little show the Sharia Indices’ movement due to the COVID-19 pandemic. This study analyzes the cointegration and contagion effect during the pandemic on Conventional and Sharia stock indices in Asia Pacific, China, Malaysia, and Indonesia. This study explores the difference between Sharia and Conventional indices during the COVID-19 pandemic. VAR (Vector Auto-Regressive) and VECM (Vector Error Correction Model) were used to analyze the hypothesis with E-Views 12. The data used in this study was the closing date from each index from 1 July 2018 to 30 June 2022. This study showed no cointegration effect between Sharia indices during the pandemic, but there was a cointegration effect on Conventional indices. During the pandemic, there was a contagion effect on both Shariah and Conventional indices. The results of this study are expected to be a reference basis for promoting the Sharia Stock Market because it is more proven in dealing with crises than the Conventional Stock Market.